IMPACT BRUISE RESISTANCE OF PALM FRUIT - Yuwana Dept. TIN (Department of Agroindustrial Technology, Bogor Agricultural University, 2008)
ABSTRACT This paper presents the dropping mass impact method to study bruise resistance and minimum absorbed energy to cause bruising on oil palm fruit, their variation values due to the differences of fruit fractions and transport delay time to palm oil processing unit. The result of the experiment indicated that the bruise volume correlated linearly with the absorbed energy produced by impact. The bruise resistance of freshly harvested fruits varied from (1.727 J/mm3) to (0.511 J/mm3) and the riper the fruit was the lower the value of bruise resistance. The bruise resistance decreased with the progress of transport delay time. The minimum absorbed energy of freshly harvested fruits ranged from 0.04 J for to 0.029 J. Generally the values of minimum absorbed energy decreased during 2 days transport delay time and then increased for all fruits except the very ripe fruit.Keywords : bruise resistance, palm fruit, transport delay time